Pengembangan Media Pembelajaran PPT Interaktif untuk Meningkatkan Pemahaman Siswa dalam Mata Pelajaran PKN di Sekolah Dasar - Fajri, Fajri Farhan; Fitra Ramadhan; Adrias Adrias; Salmaini Safitri Syam (International Forum of Researchers and Lecturers, 2025)
The rapid transformation of technology affects various aspects of life, including education. In elementary school learning, the use of interactive learning media is an innovative solution to improve student understanding. Conventional learning methods such as lectures often get bored quickly, especially if they rely only on textbooks. Therefore, teachers need to utilize technology to create more interesting and interactive media.One effective medium is interactive PowerPoint (PPT), which combines elements of sound, images, video, text, and animation to improve students' comprehension of the subject matter. It also allows for direct feedback, increases student participation, and accelerates concept understanding. In Pancasila and citizenship as a topic Education (PPKn) in elementary school, the use of interactive media has been proven to be able to increase interest in learning and encourage students' critical thinking. This study examines several studies on media efficacy using the Systematic Literature Review (SLR) technique. Interactive PPT in learning. The The results of the study indicate that the use ofthis media significantly improves students' understanding of PPKn learning. With a more interesting and interactive approach, students are more motivated to learn and able to understand concepts more deeply. Therefore, the integration of digital media in PPKn learning is an innovative solution in enhancing the caliber of education at the elementary school level